Validation of modernized questionnaire MSAQ in patients with coronary artery disease metabolic syndrome, having had percutaneous coronary intervention for acute coronary syndrome without persistent elevation of ST segment - Kholopov, Leonid Semenovich; Chumachenko, Natalia Vladimirovna; Sydorenko, Iryna Alexandrovna (Journal of Education, Health and Sport, 2016)
Kholopov Leonid, Chumachenko Natalia, Sydorenko Iryna. Validation of modernized questionnaire MSAQ in patients with coronary artery disease metabolic syndrome, having had percutaneous coronary intervention for acute coronary syndrome without persistent elevation of ST segment. Journal of Education, Health and Sport. 2016;6(1):171-178. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45171 http://ojs.ukw.edu.pl/index.php/johs/article/view/45171 https://pbn.nauka.gov.pl/works/704880 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. VALIDATION OF MODERNIZED QUESTIONNAIRE MSAQ IN PATIENTS WITH CORONARY ARTERY DISEASE METABOLIC SYNDROME, HAVING HAD PERCUTANEOUS CORONARY INTERVENTION FOR ACUTE CORONARY SYNDROME WITHOUT PERSISTENT ELEVATION OF ST SEGMENT Kholopov Leonid Semenovich (MD, PhD, Associate Professor, Cardiologist), Chumachenko Natalia Vladimirovna (Postgraduate, Cardiologist) - corresponding author, Sydorenko Iryna Alexandrovna (MD, PhD, Associate Professor, Cardiologist) Odessa National Medical University, Ukraine Vilyamsa str., 59K, app.341, Odessa, 65122, Ukraine Phone: +380632800055, e-mail: n-chumachenko@list.ru Abstract. Aim. To evaluate the quality of life and efficacy of the treatment of patients with coronary artery disease and metabolic syndrome after percutaneous coronary intervention for acute coronary syndrome without persistent ST segment elevation by adding modernized questionnaire "Modified Seattle Angina Questionnaire for patients with metabolic syndrome having had percutaneous coronary intervention” (MSAQ) to the diagnostic procedures. Materials. 94 patients took part in the research (M 61 : F 33), all of them were referred to the hospital either in clinical routine, or in connection with disease aggravation. All of them were clinically tested especially for thrombin and cortisol levels. Patients filled in the Questionnaires EQ-5D (EuroQol -5D), PHQ-8 (Personal Health Questionnaire Depression Scale) and MSAQ. Results. Patients with the results from 81 to 100% of questionnaire MSAQ (n = 26) were considered as an effective treatment group I, 61-80% (n = 49) - the group II –group of medium effectiveness of treatment and less than 60% (n = 19) – the ІІІ group –of ineffective treatment. In the group III there has been distinguished a big percent of patients independently visiting hospital on the occasion of health aggravation, 73.5% against 50.0% and 16.7% in group II and I (p <0.05), correspondingly. Veraciously big indices of thrombin were observed in group III (3.77 ± 1.29, ng / mL) and group II (4.46 ± 1.07 ng / mL) compared with group I (5.96 ± 1.89 ng / mL), (p <0.05); cortisol blood of 592.8 ± 162.9, nmol / L, 515.8 ± 84.8, nmol / L and 422.3 ± 159.2, nmol / L (p <0.05), as well as fibrinogen: 4.31 ± 1.82, g / L, 4.26 ± 2.16, g / L, 3.74 ± 1.51, g / L, (p <0.05) for III, II and I groups, respectively. Patients of the group I demonstrated high indices of living standards according to the visual – analogous scale (VAS), EQ-5D (83.8 ± 6.81, %) compared with the second (69.4 ± 9.19, %) and III (57.8 ± 10.69, %), (p <0.05) groups, respectively. There is a sustainable dynamics of increasing points on a scale PHQ-8 registered with a decrease in the effectiveness of treatment based on the results MSAQ: 10.1 ± 2.11, 14.0 ± 4.63, 18.3 ± 3.41 in the first, second and third groups, respectively, but significant (p <0.05) difference has been registered between the first and second groups only. Conclusions. MSAQ is a simple and reliable method of screening assessment of the treatment effectiveness for patients with coronary artery disease and metabolic syndrome after percutaneous coronary intervention. Keywords: modified questionnaire, metabolic syndrome, percutaneous coronary intervention.